Genetic spectrum of dyschromatosis symmetrica hereditaria in Chinese patients including a novel nonstop mutation in ADAR1 gene. Issue 1 (December 2016) - Zhang, Guolong; Shao, Minhua; Li, Zhixiu; Gu, Yong; Du, Xufeng; Wang, Xiuli; Li, Ming
Abstract Background Dyschromatosis symmetrica hereditaria (DSH) is a rare autosomal dominant cutaneous disorder caused by the mutations of adenosine deaminase acting on RNA1 (ADAR1 ) gene. We present a clinical and genetic study of seven unrelated families and two sporadic cases with DSH for mutations in the full coding sequence ofADAR1 gene. Methods ADAR1 gene was sequenced in seven unrelated families and two sporadic cases with DSH and 120 controls. Functional significance of the observedADAR1 mutations was analyzed using PolyPhen 2, SIFT and DDIG-in. Results We describe six novel mutations of theADAR1 gene in Chinese patients with DSH including a nonstop mutation p.Stop1227R, which was firstly reported inADAR1 gene. In silico analysis proves that all the mutations reported here are pathogenic. Conclusion This study is useful for functional studies of the protein and to define a diagnostic strategy for mutation screening of theADAR1 gene. A three-generation family exhibiting phenotypic variability with a single germlineADAR1 mutation suggests that chilblain might aggravate the clinical phenotypes of DSH.